The Error Analysis that Faced by Student's in Pronounce a Words - Amanda Amanda; Elsa Muliani Sukma; Yani Lubis (BADAN PENERBIT STIEPARI PRESS, 2023)
Language is part of humans since birth, one of which is English where the use of this language is widely used almost all over the world and has become an international language. In language, good and correct pronunciation of a word can affect the response that will be received by the listener. Pronunciation plays an important role in personal and social life. The purpose of this article is to find out what errors and difficulties are often experienced by students when pronouncing words in English. This study uses a qualitative method, to find the perceptions experienced by students towards errors and difficulties in pronouncing words which will then be described based on the results found. Data was collected through questionnaires and interviews which have been calculated and analyzed. The results show that many students experience errors in the pronunciation of English words due to the lack of student activities in listening such as listening to podcasts, movies, music from native speakers, and the differences in accents that students have with native speakers, and also students experience errors and difficulties in pronouncing words because there are words that sound almost the same but actually are not therefore students have difficulty distinguishing them.